The problem of the Luwian title tarwanis - Giusfredi, Federico (Altorientalische Forschungen, 2009)
This article takes into consideration the different proposals advanced so far on the origin and meaning of the Iron age Hieroglyphic Luwian title tarwanis (normally translated as “ruler”) as well as of the abstract noun tarwan(a)- and the verb tarwanaza- , by providing a complete list of all the attestations within the Neo-Hittite corpus . Advantages and weaknesses of each theory are critically examined on the levels of both etymology and semantics. In conclusion, the hypothesis of a connection to the Hittite verb tarḫ(u)- is reconsidered in light of the data we now posses about Anatolian and Luwian morphology and phonology.